Antibiotic perturbation of the human gut phageome preserves its individuality and promotes blooms of virulent phages - Eugen Pfeifer; Camille d’Humières; Quentin Lamy-Besnier; Florian Plaza Oñate; Remi Denisé; Sara Dion; Bénédicte Condamine; Marie Touchon; Laurence Ma; Charles Burdet; France Mentré; Erick Denamur; et al. (Cell Reports)
Summary: Antibiotic use disrupts the gut microbiota, posing risks of long-term health issues and resistance. To study its impact on gut phages, we followed 22 healthy individuals 2 weeks before and up to 6 months after a 3-day course of 3rd-generation cephalosporins. Our results show that gut phages rarely encode antibiotic resistance genes and are mostly temperate, including many phage plasmids. Furthermore, phage populations remain individual-specific even after microbiome perturbation. Yet, we report a 20% decline in phage diversity the day after treatment, alongside blooms of a few, mostly virulent, phages. We suggest that some of these phages contribute to the recovery of bacterial diversity via “kill-the-winner” dynamics. This is supported by (temporarily) dominant phages targeting Parabacteroides distasonis, a bacterium that thrives post-treatment only in the absence of these phages. Our findings suggest gut phages are crucial to the microbiome response to antibiotics, aiding the restoration of balance and diversity.